Contribution of soil fertility replenishment agroforestry technologies to the livelihoods and food security of smallholder farmers in central and southern Malawi - Quinion, Ann Farrington (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScFor (Forest and Wood Science))--Stellenbosch University, 2008.